THE PREVALENCE OF METABOLIC DISORDERS AND HYPERTENSION IN WOMEN DURING PERIMENOPAUSE AND MENOPAUSE - Smiljić, Sonja; Šapić, Srna; Nestorović, Vojkan; Milanović, Zvezdan; Dejanović, Mirjana; Karanović, Andrijana (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Cardiometabolic diseases, including type 2 diabetes (T2D) and cardiovascular disease, and their associated factors, such as hypertension, dyslipidemia, insulin resistance, and obesity, are among the leading causes of morbidity and mortality. At a young age, the prevalence of cardiometabolic diseases is higher in men than in women, but this female advantage gradually disappears with aging, particularly after menopause, when cardiometabolic risk factors accumulate.Our research aimed to highlight the prevalence of metabolic disorders and their association with hypertension in women during perimenopause and menopause.Method: The study included 200 middle-aged women: 131 (65.5%) perimenopausal women who had experienced typical perimenopausal signs for more than 6 months, and 69 (34.5%) menopausal women with absent menstrual cycles for more than 12 months, aged 50-59 years. The patients visited their physician for a routine preventive examination in December 2024. Results: Hypertension was statistically significantly more common in women in menopause (84.1%) compared to premenopausal women (p < 0.001). Women in menopause had significantly higher rates of metabolic disorders, increased body mass and obesity, with 66.7% of the participants affected, as well as a larger waist circumference in 63.8% of the participants (p = 0.003). Menopausal women had statistically significantly higher levels of triglycerides, LDL cholesterol, and total cholesterol than premenopausal women (p = 0.002). Among women going through menopause, diabetes mellitus was statistically substantially more prevalent, affecting 27% of them (p = 0.002). Premenopausal women had a statistically significantly greater prevalence of hypothyroidism (14.7%) than did menopausal women (4.3%) (chi-square = 4.905, p = 0.027). These two groups of participants did not differ significantly in terms of sedentary habits, smoking, or family history of hypertension. Conclusion: Type 2 diabetes, obesity, dyslipidaemia, and hypertension were all substantially more common in menopausal women. Preventive screenings are therefore crucial for women going through menopause and perimenopause to promptly detect and treat cardiometabolic disorders and prevent more serious cardiovascular diseases.
Keywords: menopause; hypertension; cardiometabolic disorder